2020
DOI: 10.1145/3414685.3417844
|View full text |Cite
|
Sign up to set email alerts
|

Freeform quad-based kirigami

Abstract: Kirigami, the traditional Japanese art of paper cutting and folding generalizes origami and has initiated new research in material science as well as graphics. In this paper we use its capabilities to perform geometric modeling with corrugated surface representations possessing an isometric unfolding into a planar domain after appropriate cuts are made. We initialize our box-based kirigami structures from orthogonal networks of curves, compute a first approximation of their unfolding via mappings between meshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…One way to easily construct spatial shapes from flat sheets is by appropriately folding paper [Dudte et al 2016;Massarwi et al 2007], which is inherently related to the Japanese art of Origami. Also Kirigami, a technique to cut patterns into planar sheets to allow solid faces to rotate about each other, deforming in three dimensions while remaining planar has been explored for deployable surfaces [Jiang et al 2020;Liu et al 2020] and recently also bi-stable structures .…”
Section: Related Workmentioning
confidence: 99%
“…One way to easily construct spatial shapes from flat sheets is by appropriately folding paper [Dudte et al 2016;Massarwi et al 2007], which is inherently related to the Japanese art of Origami. Also Kirigami, a technique to cut patterns into planar sheets to allow solid faces to rotate about each other, deforming in three dimensions while remaining planar has been explored for deployable surfaces [Jiang et al 2020;Liu et al 2020] and recently also bi-stable structures .…”
Section: Related Workmentioning
confidence: 99%
“…Previous work has demonstrated that the checkerboard kirigami pattern can be used to approximate almost any form of curved surface. [ 43 ] However, its mechanical properties under external loads are still uncovered. Herein, we are primarily interested in both the mechanical strength and shape‐transforming of the checkerboard kirigami.…”
Section: Introductionmentioning
confidence: 99%
“…The previous works mostly focus on varying the sizes and orientations of cuts under fixed connections on an intact sheet without defects such as holes or cracks, that is, the topology of the sheet is fixed. The kirigami patterns perforated on flat sheets with flexible topologies are investigated in [20][21][22][23][24], where the deployability is realized by folding to close the cutting holes. Conversely, many other kirigami structures are deployed in the way of opening cuts, among which the quadrilateral tessellations are extensively used to achieve unique properties such as reconfigurability [16,25], high stretchability [26,27], and auxeticity [28,29].…”
Section: Introductionmentioning
confidence: 99%